P050: The Northern Amazing and Awesome Model: Using positive deviance to impact patient care. (May 2020) - Ohle, R.; McIsaac, S.
Abstract : Introduction: Positive deviance recognizes that there are individuals and teams within our community of practice that succeed in spite of system constraints. Amazing and awesome rounds has been proposed as a forum to identify behaviours and processes that lead to exceptional results. The objective of this study was to determine the feasibility and acceptability of a structured amazing and awesome rounds model through an innovative educational intervention. Methods: The authors engaged a broad range of professional designations(physicians, surgeons, nurses, respiratory therapists, administrative staff) at a tertiary care institution. A&A rounds were open to all allied health professionals and administrative staff. The Northern A&A rounds model was developed, implemented, and then evaluated as a four-part intervention. This consisted of: 1) Allied health professional training on case selection and analysis, 2) Engaging inter professional members, 3) disseminating lessons learned, and 4) creating an administrative pathway for acting on issues identified through the A&A rounds. The measures of intervention feasibility included the proportion of sessions adherent to the new model and A&A rounds attendance. Post intervention surveys of presenters and attendees were used to determine intervention acceptability. A&A presentation content was reviewed to determine the most frequently adopted components of the model. Results: Nine out of 9(100%) of presented cases were adherent to the three components of the Northern A&A Model. A&A rounds were highest attended of all hospital wide grand rounds(N = 75 SD 2.4 P < 0.001). Nine case presentations were analyzed and 7 action items were identified for amplification across the hospital. Including 3 case reports published of a novel approach to a patient case, a rapid referral for trauma patients at risk for PTSD, AED placement in all community clinics and routine debrief after resuscitations. Presenters included a broad representation of hospital staff including surgeons, emergency physicians, radiologists, nurses, and administrators. Conclusion: The Northern A&A Model was a feasible intervention that was perceived to be effective by both presenters and attendees. The authors believe that this could be readily applied to any hospital seeking to enhance quality of care and patient safety.